Implementasi Program Genre: Strategi Duta Genre Dalam Pencegahan Penyalahgunaan Napza di Kalangan Remaja di Kota Banda Aceh - Fitrianti, Fitrianti; Juaris, Juaris (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2024)
The Generasi Berencana Program (Genre) is a government`s policy as an effort to solve population proplem in Indonesia. the main focus of the program is to educate teenagers to avoid the risk of adolescent diseases such as sexual diseases due to premarital sex behavior, Human Human Immunodeficiency Virus (HIV) / Acquired Immune Deficiency Syndrome (HIV/AIDs), NAPZA (narcotics, psychotropichs and addictive substances), so that they become a strong and visionary Indonesian teenager. This study aims to examine the strategy of implementing the Genre program by Genre ambassadors as an effort to prevent drug abuse among teenagers in Banda Aceh city. The research method uses a descriptive qualitative method with interviews, observations and documentation as data collection techniques. Then, data analysis is caried out using the Miles and Huberman (2014) method namely reduction, data presentation, and drawing conclusions. The results of the study show that the Aceh Genre Forum (FGA) ambassador which is under the coordination of BKKBN has taken various steps as an effort to implement the Genre program to prevent drug abuse by adolescent in Banda Aceh city. The strategies are education and socialization through seminar and training, adolescent and parents approach strategies which is PIK R/M and BKR, the use of media both conventional dan new/social media such as newspaper, radio, Instagram, and Tik Tok as well as collaborating with partners at the local, national dan international levels.